The Burden of Education Costs for the Middle Class in Indonesia: An Analysis of Challenges and Implications - Budhy Nagara, Khaerul; Rusma Rizal , (Jurnal Serambi Ilmu, 2025)
This study examines the rising education costs in Indonesia and their impact on middle-class families who serve as the backbone of the nation’s economy and social structure. The research aims to identify the definition and characteristics of the middle class, analyze the structure and trends of increasing education expenses, and assess the financial burdens they face. Using a descriptive qualitative approach, the study explores how the escalating costs—comprising tuition fees, development contributions, living expenses, and hidden costs—place middle-class families in a disadvantaged position. The findings reveal that these families often fall into a “squeezed middle” condition: ineligible for poverty-targeted assistance yet unable to comfortably afford high-quality education. This financial strain limits accessibility, weakens human resource quality, reduces social mobility, and creates risks for long-term national economic development. In response, families adopt adaptation strategies such as long-term financial planning, saving and investing, seeking scholarships, and improving financial literacy. At the policy level, comprehensive interventions are required to balance affordability and quality. The conclusion emphasizes that addressing education costs is critical to ensuring equitable access, supporting social mobility, and strengthening Indonesia’s pathway toward sustainable national development.